Analisis Pengaruh Kepuasan Kerja dan Beban Kerja terhadap Kinerja Karyawan pada Bank Syariah Indonesia Muara Tembesi Kabupaten Batang Hari - Niki Kosasih; Sumantri Sumantri (Universitas Batanghari Jambi, 2026)
The aim of this research is to explain the influence of job satisfaction and workload on employee performance at Bank Syariah Indonesia Muara Tembesi, Batang Hari - Jambi Regency. The method used is a quantitative method using multiple linear regression analysis tools, testing the significance of the influence of the variables job satisfaction (X1) and workload (X2) as independent variables and employee performance (Y) as the dependent variable using the t test and F test. The test results on the influence of job satisfaction and workload on employee performance obtained a calculated F value of 11,649 > F table 3,27 with a significance level of 0.05, so it is proven that there is a joint and significant influence of job satisfaction and workload on employee performance. The determination test shows that the combined influence of job satisfaction and workload on employee performance at Bank Syariah Indonesia Muara Tembesi is 0.365 or 36.5% and the remaining 0.63.5 or 63.5% is influenced by other variables not examined in this study.